A Fuzzy Cognitive Map system to explore certain scenarios on the Cyprus banking system - Papaioannou, Maria C.; Neocleous, Costas; Papageorgiou, Charalambos; Schizas, Christos N. (My University, 2014)
The model of Fuzzy Cognitive Maps (FCMs) allows a user to investigate how the influencing parameters of a cause-effect system behave under the implementation of desired scenario. Human knowledge and experience is used to define the structure and the parameters of a FCM model. This paper proposes a methodology which smoothly directs the steps that the experts should take in building an FCM system in order to reduce the subjectivity which characterizes such expert systems. Furthermore, an update rule for the parameters during the simulation phase is presented. Finally, the novel FCM construction methodology and the proposed FCM update rule are tested on a real-life system to investigate the repercussions of the combination of the Greek private sector involvement (PSI) with the decrease of people's confidence towards the Cyprus banking system. The results resemble what actually happened to the Cyprus economy a short period after the implementation of the Greek PSI.
Keywords: Fuzzy Cognitive Maps; Intelligent systems; Private sector involvement